2012
DOI: 10.2174/157340612799278351
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Glass Ionomer Cements on Human Dental Pulp Stem Cells Correlate with Fluoride Release

Abstract: Fuji Plus, Vitrebond and Fuji VIII, which released fluoride in higher quantities than other GICs, were highly toxic to human DPSCs. Opposite, low levels of released fluoride correlated to low cytotoxic effect of Composit, Fuji I and Fuji Triage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 21 publications
3
42
1
4
Order By: Relevance
“…Cytotoxicity of phosphate cements has been attributed to the release of zinc ions and other chemical substances 22) . Similarly, it has been suggested that GICs, which released fluoride in high quantities, were highly toxic to human dental pulp stem cells 23) . Contrarily, Stanislawski et al reported that the concentration of F − , Sr 2+ and Al 3+ in the elutes of GICs was too low to be cytotoxic and suggested that the principal compounds responsible for cytotoxicity of RMGICs are unpolymerized resin monomers 2) .…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity of phosphate cements has been attributed to the release of zinc ions and other chemical substances 22) . Similarly, it has been suggested that GICs, which released fluoride in high quantities, were highly toxic to human dental pulp stem cells 23) . Contrarily, Stanislawski et al reported that the concentration of F − , Sr 2+ and Al 3+ in the elutes of GICs was too low to be cytotoxic and suggested that the principal compounds responsible for cytotoxicity of RMGICs are unpolymerized resin monomers 2) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some dental luting cements are cytotoxic to the dental pulp cells and cause hypersensitivity in animal studies [7]. There have also been numerous biocompatibility studies of dental luting cement using cell culture techniques with various cells, such as gingival fibroblasts [8], dental pulp cells [9,10] and mouse fibroblasts [11]. However, all of the previous studies focused on the viability of the cells as the method of cytotoxicity evaluation for dental cements, method which have often been criticized due to the poor correlation with either animal studies or clinical results, as it does not reflect inflammatory mechanisms of the body system [12].…”
Section: Introductionmentioning
confidence: 99%
“…We speculated that this may be related to the cytotoxicity of fluoride. Many studies have shown that the effect of the high concentration of fluoride may cause cell apoptosis, in multiple cell types including hepatocytes [25], human embryo hepatocytes [26], human dental pulp stem cells [27], peripheral blood mononuclear cells [28], and osteoblasts [29]. Thus, we speculated that at higher concentrations of fluoride there may also be induction of B cell apoptosis.…”
Section: Discussionmentioning
confidence: 94%